Analisa Pengaruh BOPO, Kecukupan Modal, Pembiayaan Bermasalah, Bagi Hasil Dan Profitabilitas Terhadap Simpanan Mudharabah Pada Bank Umum Syariah Periode 2011-2015 - Sisca Juliana; Ade Sofyan Mulazid (Institut Agama Islam Negeri Kendari, 2017)
This study aims to determine the effect BOPO Effect Analysis, Capital Adequacy, Troubled Financing,Sharing and Profitability simultaneously and partially to rate Deposits at Commercial Bank SyariahMudharabah period 2011-2015. There are nine samples in this study who met the study criteria, namelyBank BCA Syariah, Bank BRI Syariah, Bank BNI Syariah, Bank Muamalat Indonesia, Bank SyariahMandiri, Bank Mega Syariah, Bank Panin Syariah, Bank Syariah Bukopin and Bank BJB Syariah. Theanalytical tool used is a panel data regression analysis. The model chosen is Random Effect are tested by Ftest and t test, with significance level of 5%. Result of test F known that ROA, CAR, NPF, Sharing and ROAsimultaneously affect the Deposit Mudharabah Islamic Banks. Based on the test results t is known that,CAR does not affect the Deposit Mudharabah. ROA, NPF, Sharing and ROA significant positive effect onMudharabah Savings on Islamic Banks. Adjusted R Square in this study indicate that the variable ROA,CAR, NPF, Sharing and ROA in explaining the dependent variable Mudharabah Savings amounted to66.50% while the remaining 33.50% influenced by other independent variables that are not used in this study.